2007
DOI: 10.1073/pnas.0705963104
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor outer segment phagocytosis attenuates oxidative stress-induced apoptosis with concomitant neuroprotectin D1 synthesis

Abstract: Photoreceptor cell (rods and cones) renewal is accompanied by intermittent shedding of the distal tips of the outer segment followed by their phagocytosis in the retinal pigment epithelial (RPE) cells. This renewal is essential for vision, and it is thought that it fosters survival of photoreceptors and of RPE cells. However, no specific survival messenger/mediators have as yet been identified. We show here that photoreceptor outer segment (POS) phagocytosis markedly attenuates oxidative stress-induced apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 35 publications
2
100
0
1
Order By: Relevance
“…Because NPD1 counteracts oxidative stress-induced apoptosis and also up-regulates the anti-apoptotic protein Bcl-x L in ARPE-19 cells (3), it was proposed that NPD1 may act at the transcriptional, translational, and posttranslational level to regulate the anti-apoptotic activity of Bclx L . In a previous report, it had been shown that after 1 h of serum starvation and 6 h of 400 and 800 M H 2 O 2 /TNF␣ induction, total Bcl-x L protein was down-regulated, and 50 nM NPD1 up-regulated this protein (4,5). The activated (phosphorylated) form of this protein has until now not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because NPD1 counteracts oxidative stress-induced apoptosis and also up-regulates the anti-apoptotic protein Bcl-x L in ARPE-19 cells (3), it was proposed that NPD1 may act at the transcriptional, translational, and posttranslational level to regulate the anti-apoptotic activity of Bclx L . In a previous report, it had been shown that after 1 h of serum starvation and 6 h of 400 and 800 M H 2 O 2 /TNF␣ induction, total Bcl-x L protein was down-regulated, and 50 nM NPD1 up-regulated this protein (4,5). The activated (phosphorylated) form of this protein has until now not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Single plane images were taken using a DIAPHOT 200 microscope (Nikon, Melville, NY) with fluorescence optics. Images were recorded using a Hamamatsu color chilled 3CCD camera (Bridgewater, NJ) and PhotoShop software, Version 5.0 (Adobe Systems, Mountain View, CA) (5,10). (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental phagocytosis of photoreceptor outer segments and polystyrene microspheres showed that RPE cells fed only with outer segments were more resistant to oxidative stressinduced apoptosis [20]. On the other hand, RPE cells that effectively phagocytized microspheres when exposed to oxidative stress showed apoptosis.…”
Section: Photoreceptor Outer Segment Phagocytosis Selectively Attenuamentioning
confidence: 99%
“…These noxious stimuli further orchestrate pathogenic gene-expression programs in stressed brain cells, thereby linking a cascade of cell death pathways with apoptosis and neuronal demise. Neural mechanisms leading toward NPD1 generation from DHA thereby appear to redirect cellular fate toward successful preservation of RPE-photoreceptor cell integrity [10,20,26] and brain cell aging [25]. The Bcl-2 pro-and antiapoptotic gene families, sAPP alpha (and/or other neurotrophins) and NPD1, lie along a cell fate-regulatory pathway whose component members are highly interactive, and have potential to function cooperatively in brain and retina cell survival.…”
Section: Agingmentioning
confidence: 99%
“…A property of PPAR-α which adds further clinical potential to our findings is that PPAR-α is also known to influence the activity of key functional components, such as vascular endothelial growth factor (VEGF), docosahexanoeic acid (DHA), and matrix metalloproteinases (MMP), which participate in the progression of AMD and are themselves possible targets for therapeutic intervention (13,14). DHA has been shown to be critical for maintaining the integrity of photoreceptors (34), and its protective effect on RPE cells to oxidative stress is mediated by neuroprotectin D1 (NPD1), a derivative of DHA, that possesses antiapoptotic and antiinflammatory properties (35,36). The first evidence that an IPC-like response was involved in the sulindac protective effect was that the protection was also dependent on PKCe as demonstrated by a loss of sulindac protection when cells were treated with either a nonspecific PKC blocker or a specific PKCe peptide inhibitor.…”
Section: Discussionmentioning
confidence: 99%